Settimo anno. Presentazione del libro di Massimo Fagioli, Roma, 11 ottobre 2013 - Vari, Autori (Il sogno della farfalla, 2014)
On October 11th 2013 the book which brings together the lectures on psychodynamic psychology that Massimo Fagioli held at the University of Chieti in 2008 was presented at the Feltrinelli Bookshop of Rome. The talks delivered by Gianfranco De Simone and Daniela Polese, both psychiatrists and psychotherapists, by Martina Patanè, physician, and by Fagioli himself retrace the train of thought running through the lessons. By engaging in the story and topicality of this continuous research, a number of themes emerge such as the proposal of a medical methodology to be applied to psychiatry, the clash with religious thinking as well as rational thinking, the dialectic with the left, the realization of a new “female image”.